Optimal charging of electric vehicles considering constraints of the medium voltage distribution network - Garcia-Osorio, Victor A. [UNESP]; Rueda-Medina, Augusto C. [UNESP]; Melo, J. D. [UNESP]; Padilha-Feltrin, Antonio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
The scope of this work is to optimize the charging of electric vehicles (EVs) in a controlled environment. The method uses a linear optimization technique, which determines the electrical power that will be delivered to each EV considering as constraints the operating levels of the medium voltage distribution network. The proposed method was tested using the IEEE 34 bus distribution test system considering a level of penetration of EVs of 15%. The results show that, using the optimization process, it is possible to attend the demand of all considered PHEVs without violating any constraints. © 2013 IEEE.
Keywords: distribution systems; electric vehicles; Linear optimization; optimal charging rate; Controlled environment; Distribution systems; Electric Vehicles (EVs); Electrical power; Medium-voltage distribution networks; Operating levels; Optimal charging; Electric power distribution; Electric vehicles; Smart power grids; Optimization